Size Designation System of Clothes and Footwear Based on Croatian Anthropometric System (Journal of Fiber Bioengineering and Informatics, 2018)
The compound technological project Croatian Anthropometric System is a national project. Theanthropometric measurement of the population of the Republic of Croatia was performed within thisproject with the aim of adopting the Croatian Anthropometric System as the basic document for thesize designation system of clothes and footwear. The measurements of anthropometric characteristicsas well as collecting data under social and economic conditions were carried out by previous teams.The successful implementation of this project includes strategic planning, which includes an adequateselection of associates, planning and proper organization, precise distribution of tasks, synchronizationof the dynamics of their performances and interactive way of managing the project implementationprocess. In managing research projects, a strategic management approach also includes the connectionand harmonization of diverse knowledge, specific methodologies and specific professional interests ofmembers of a (often multidisciplinary) team of scientific and professional associates, and maintainingthe consistency of the methodology of research.